Protecting Agriculture The Legal Basis of Regulatory Action in Florida - Fegan, Regina M (Plant disease, 2004)
The Division of Plant Industry of the Department of Agriculture and Consumer Services of Florida is empowered to protect the state's agriculture from both introduction and intrastate movement of pests. This responsibility is shared by similar regulatory agencies of the federal government and other states. The legal basis of such regulatory action, police power and eminent domain, is reviewed. The regulatory processes by the State of Florida of two important citrus pests, the burrowing nematode and Asiatic citrus canker, are presented. It was concluded that Florida's regulatory power to take property is of great importance to the agricultural industry and to Florida's economy. This power must be exercised within the constitutional limitation that "no person shall be deprived of life, liberty, or property without due processes of law." However, the imminence of an emergency may justify state action without a prior hearing or just compensation of valueless items